A fox called Sorrow - Carmody, Isobelle (New York , Random House, 2006)
n a dangerous quest to the troll city of Underth, the healer, Little Fur, is mystified by a new companion--a scarred and angry fox whose strong spirit keeps him alive despite his wish to die